Kebijakan Modal Kerja, Manajemen Kas, Manajemen Piutang, dan Manajemen Persediaan terhadap Optimalisasi Kinerja Laba pada Industri Farmasi yang Terdaftar di Bursa Efek Indonesia - Aditya Gunawan Syamsuddin; Abdul Rahman; Muhammad Sobarsah (Magister Management, Hasanuddin University, 2019)
This study aims to determine and analyze the effect of working capital policies, cash management policies, debt management policies, inventory management policies and the influence of the average cash balance on profit performance optimization in the Pharmaceutical Industry listed on the Indonesia Stock Exchange. The study uses secondary data with the use multiple linear regression analysis. Classical assumption test are conducted to mee the prerequisite of regression analysis. The results of the study found that the efficiency ratio of earnings performance in Pharmaceutical Companies observation period in 2007-2016 showed that there was a positive and significant influence between efficiency ratios on increasing earnings performance. The effect of cash turnover on earnings performance where in the findings of this study found that cash turnover has a negative and not significant effect on pharmaceutical companies because the proportion of increase in cash turnover is not in line with the increase in profit performance (ROA). The effect of accounts receivable turnover on earnings performance, where the findings in this study found that empirically there was a positive and significant influence between accounts receivable turnover to profit performance (ROA). The effect of inventory turnover on earnings performance in Pharmaceutical companies with the observation period of 2007 - 2016, where in this study found that inventory turnover can have a significant effect on the increase in profit performance (ROA). The effect of the average cash balance on earnings performance in Pharmaceutical Companies listed on the Indonesia Stock Exchange. This gives the finding that empirically there is a positive and significant influence between the average cash balance on earnings performance in pharmaceutical companies with the observation period of 2007 - 2016.